عالمی سیاست میں معاندانہ رویوں کے عروج کا قرآنی حل: اسلامی اقدار اور جدید رویوں کا تقابلی تجزیہ: The Qur'anic Solution to the Rise of Hostile Attitudes in Global Politics: A Comparative Analysis of Islamic Values and Modern Attitudes - Zakir, Dr. Muhammad; Dr Rizwana Gul , Dr Rizwana Gul; Mahmood, Dr. Khalid (Al-Amīr Research Journal for Islamic Studies, 2024)
In today's global political landscape, the rise of hostile attitudes and divisive rhetoric has created significant challenges to peace and cooperation. This research explores the Qur'anic approach to addressing such hostility by examining the core values of Islam and contrasting them with modern political behaviors. The need for this study stems from the increasing polarization in international relations and the growing gap between moral principles and political practice.The objective of this research is to investigate how Qur'anic teachings on patience, justice, and reconciliation can offer a solution to contemporary political hostility, and to compare these values with the often adversarial and pragmatic attitudes prevalent in modern politics. This study aims to highlight the potential for Islamic values to contribute to a more harmonious and cooperative global order. The expected results will provide a comprehensive understanding of how Islamic teachings can be applied to mitigate hostility in global politics and foster a culture of mutual respect and dialogue. By offering a comparative analysis, this research will present an alternative framework for addressing political tensions in the modern world. Keywords: Qur'anic solutions, global politics, hostility, Islamic values, modern attitudes.